Two New Ways To Slash Transportation Costs (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Ask any mineral industry executive what he considers one of the most expensive aspects of getting a product to the ultimate consumer and invariably the answer will be transportation. Some company officials say that transportation charges alone account for over half of the total cost of most products. If these judgments are correct and a recent invention turns out to be the long-awaited breakthrough that shippers have been looking for, then many producers can look forward to slashing their delivery costs by 90%.